Commercial porcine reproductive and respiratory syndrome virus (PRRSV)‐2 modified live virus vaccine against heterologous single and dual Korean PRRSV‐1 and PRRSV‐2 challenge. (28th April 2018) - Jeong, Jiwoon; Kim, Seeun; Park, Changhoon; Park, Kee Hwan; Kang, Ikjae; Park, Su‐Jin; Chae, Chanhee
Abstract : This study evaluated porcine reproductive and respiratory syndrome virus (PRRSV)‐2 modified live virus (MLV) vaccine against heterologous single and dual challenge of Korean PRRSV‐1 and PRRSV‐2. Pigs were administered PRRSV‐2 MLV vaccine intramuscularly at 21 days of age and inoculated intranasally with both genotypes at 56 days of age. Vaccination of pigs with PRRSV‐2 MLV vaccine resulted in reduction of viral loads of both PRRSV‐1 and PRRSV‐2 after heterologous single and dual challenge with PRRSV‐1 and PRRSV‐2. In addition, pigs vaccinated with PRRSV‐2 MLV vaccine exhibited higher frequencies of PRRSV‐1 and PRRSV‐2 specific interferon‐γ secreting cells (IFN‐γ‐SC) and showed a significant reduction in lung lesions and PRRSV nucleic acid within the lung lesions after single and dual challenge compared with unvaccinated challenged pigs. Taken together these results demonstrated that vaccination of pigs with PRRSV‐2 is efficacious in protecting growing pigs from respiratory disease against heterologous single and dual PRRSV‐1 and PRRSV‐2 challenge.